Optical control of transverse motion of ionization injected electrons in a laser plasma accelerator. (18th January 2021) - Feng, Jie; Li, Yifei; Wang, Jinguang; Li, Dazhang; Zhu, Changqing; Tan, Junhao; Geng, Xiaotao; Liu, Feng; Chen, Liming
Abstract: We demonstrate an all-optical method for controlling the transverse motion of an ionization injected electron beam in a laser plasma accelerator by using the transversely asymmetrical plasma wakefield. The laser focus shape can control the distribution of a transversal wakefield. When the laser focus shape is changed from circular to slanted elliptical in the experiment, the electron beam profiles change from an ellipse to three typical shapes. The three-dimensional particle-in-cell simulation result agrees well with the experiment, and it shows that the trajectories of these accelerated electrons change from undulating to helical. Such an all-optical method could be useful for convenient control of the transverse motion of an electron beam, which results in synchrotron radiation from orbit angular momentum.